CYTOARCHITECTURE OF THE ADENOHYPOPHYSIAL FOLLICULOSTELLATE CELL OF THE MALE FLAT HEADED BAT, TYLONYCTERIS PACHYPUS (TEMMINCK) - BORKAR, MANOJ. R.; MANTRI, U.U.; AVARI, K.M..; RAUT, P. D.; BHIWGADE, D.A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
The ultrastructure of the agranular folliculo-stellate cell from the adenohypophysis of the male flat headed bat Tylonycteris pachypus (Temminck) is described here. The cell is characterized by the presence of large, bizzare nucleus, a capacious extra-vascular cavity and underdeveloped cell organelles. In the light of the ultrastrucutral findings the functional role of this cell is discussed.